The South Asian religious diaspora in Britain, Canada, and the United States - Coward, Harold G.; Hinnells, John R.; Williams, Raymond Brady (SUNY series in religious studies., 2000)
Scholars of religion in general and specific religions were recruited as contributors, presented first drafts in London in 1996, and revised their essays according to its reception. They explore the experience of religious communities that have migrated to the three English- speaking countries, considering the cultural nuances of each, how traditions are reformed or reinvented, and how they are passed on through the family and institutions. They mainly focus on Hindus, Muslims, and Sikhs but also include Christian, Zoroastrian, and other immigrants and new religious movements in the west led by south Asians. Annotation copyrighted by Book News, Inc., Portland, OR.